2008
DOI: 10.1111/j.1467-9280.2008.02104.x
|View full text |Cite
|
Sign up to set email alerts
|

Explaining Contradictory Relations Between Risk Perception and Risk Taking

Abstract: Different studies have documented opposite relations between perceived risk and behavior. The present study tested a theoretical explanation that reconciles these conflicting results. Adolescents (N= 596) completed alternative measures of risk perception that differed in cue specificity and response format. As predicted by fuzzy-trace theory, measures that emphasized verbatim retrieval and quantitative processing produced positive correlations between perceived risk and risky behavior; risk perceptions reflect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
238
3
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 160 publications
(264 citation statements)
references
References 15 publications
18
238
3
5
Order By: Relevance
“…Esto significa que las personas que perciben más riesgos en una conducta se ven más disuadidas de llevarla a cabo; del mismo modo, las personas que perciben pocos riesgos en una conducta se ven más motivadas para implicarse en ella. Este patrón mostraría la percepción de riesgos como una variable protectora de la salud (Mills, Reyna y Estrada, 2008).…”
Section: * Dirección Para Correspondencia [Correspondence Address]unclassified
See 1 more Smart Citation
“…Esto significa que las personas que perciben más riesgos en una conducta se ven más disuadidas de llevarla a cabo; del mismo modo, las personas que perciben pocos riesgos en una conducta se ven más motivadas para implicarse en ella. Este patrón mostraría la percepción de riesgos como una variable protectora de la salud (Mills, Reyna y Estrada, 2008).…”
Section: * Dirección Para Correspondencia [Correspondence Address]unclassified
“…Esto significa que las personas que perciben más riesgos en una conducta se ven más disuadidas de llevarla a cabo; del mismo modo, las personas que perciben pocos riesgos en una conducta se ven más motivadas para implicarse en ella. Este patrón mostraría la percepción de riesgos como una variable protectora de la salud (Mills, Reyna y Estrada, 2008).Sin embargo, los resultados de la investigación han arrojado conclusiones contradictorias y sugieren que la relación entre la percepción de riesgo y la conducta arriesgada no es tan clara y sencilla como podría parecer en un primer momento. En este sentido, Horvath y Zuckerman (1993) han constatado que no siempre una conducta arriesgada se lleva a cabo como consecuencia de no percibir adecuadamente los peligros que entraña sino que, en ocasiones, la evaluación es posterior a la conducta.…”
unclassified
“…Periodic or ongoing use of alcohol and other drugs among adolescents is frequently associated with increased risk-taking, but also with the limited insight into the nature of those risks [19]. However, studies of adolescent risk perception, versus risk behavior, have shown that the endorsement of simple values and principles provided the greatest protection against risk-taking [20]. Comprehensive data on specifi c sexual risk-taking behavior among HIVpositive and -negative adolescents was reported from the multisite REACH (Reaching for Excellence in Adolescent Care and Health) cohort [21].…”
Section: Behavioral Factorsmentioning
confidence: 97%
“…The classic psychological theories suggest people's decision on risk-taking behavior is negatively correlated with their risk perception [7]. Thus, individuals who are weak in risk perception or tend to misestimate the risks are vulnerable to safety hazards.…”
Section: Introductionmentioning
confidence: 99%